The mystery of Antarctic climate change and its relation to geomagnetic field - Kilifarska, N.A.; Bakhmutov, V.G.; Melnyk, G.V. (Український антарктичний журнал, 2013)
The regional characteristics of changing climate are serious challenge for the current understanding regarding the driving factors of climate variability. Here we present a plausible explanation for the diversity of regional response of Antarctic climate to uniform enhancement of greenhouse gases, i.e. the simultaneous warming of the Western and cooling of the Eastern Antarctica. The explanation is related to the heterogeneously distributed geomagnetic field, controlling the intensity and depth of particles penetration in the Earth’s atmosphere.